Pengembangan Produk Sagu Melalui Pendekatan Klaster Inovasi - Gevisioner; Ismon Zakia; Elnovarian Purnama; Heryudarini Harahap (Jurnal Kebijakan Pembangunan dan Inovasi, 2019)
The low quality of sago flour is still low, until now it is still a major problem in the sago flour processing industry in Riau Province. This has an impact on the low value-added and competitiveness of sago products. To obtain a solution to this problem, collaboration/partnership between academics, business (business), government, and community (community) sago (ABG + C) partnerships are needed. One effort to develop sago products is to formulate the development of sago products through an innovation cluster approach. The method used in this study is a field survey and Focus Group Discussion. The survey was conducted in 2 (two) districts of Indragiri Hilir and Meranti Islands. The results of the study indicate that the development of innovation-based industries must be implemented in a sustainable manner, through the main activities: 1) Development of Dry Sago Flour Refineries, 2) Training and Technology and Managerial Assistance, 3) Growth of Downstream Sago Flour Downstream Industry.